Early Warning and Conflict Resolution - Adam, Absalom M. (Refuge: Canada’s Journal on Refugees, 1994)
An Essay Review. Early Warning and Conflict Resolution. Edited by Michiko Kurda and Kumar Rupesinghe. New York: St. Martin’s Press. Inc., 1992; xxv-238.